2017
DOI: 10.1371/journal.pone.0177870
|View full text |Cite|
|
Sign up to set email alerts
|

The mediating role of rumination in the relation between attentional bias towards thin female bodies and eating disorder symptomatology

Abstract: The present study sought to investigate the association between selective attentional processing of body images, rumination, and eating disorder symptoms in young women. Seventy-three undergraduate female students (ages 17–24) completed a modified dot-probe task to assess whether young women showed a differential attentional bias pattern towards thin and non-thin female bodies. Participants also completed self-report measures of eating disorder pathology. It was found that increased reports of dietary restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 49 publications
5
57
5
Order By: Relevance
“…Our findings also dovetail with earlier work by Jansen and colleagues who found that women with higher levels of eating disorder symptoms show an overestimation of the thinness of other women's bodies and lack a self-serving bias when rating the attractiveness of their own bodies (Alleva et al, 2013;Jansen, Smeets, Martijn, & Nederkoorn, 2006). Finally, our results are in line with previous research, suggesting that women with elevated eating disorder symptoms tend to selectively attend towards thin/attractive other women and towards non-thin/unattractive parts of their own body (Cho & Lee, 2013;Dondzilo, Rieger, Palermo, Byrne, & Bell, 2017;Jansen, Nederkoorn, & Mulkens, 2005;Roefs et al, 2008). Taken together, this underscores the notion that women feature differential patterns of implicit evaluation regarding one's own and other women's bodies.…”
Section: F I G U R Esupporting
confidence: 92%
“…Our findings also dovetail with earlier work by Jansen and colleagues who found that women with higher levels of eating disorder symptoms show an overestimation of the thinness of other women's bodies and lack a self-serving bias when rating the attractiveness of their own bodies (Alleva et al, 2013;Jansen, Smeets, Martijn, & Nederkoorn, 2006). Finally, our results are in line with previous research, suggesting that women with elevated eating disorder symptoms tend to selectively attend towards thin/attractive other women and towards non-thin/unattractive parts of their own body (Cho & Lee, 2013;Dondzilo, Rieger, Palermo, Byrne, & Bell, 2017;Jansen, Nederkoorn, & Mulkens, 2005;Roefs et al, 2008). Taken together, this underscores the notion that women feature differential patterns of implicit evaluation regarding one's own and other women's bodies.…”
Section: F I G U R Esupporting
confidence: 92%
“…These results complement the findings of previously described studies finding that fear of the overweight self was more strongly related to eating pathology than the pursuit of thinness (Dalley, 2016;Dalley & Buunk, 2009;Dalley et al, 2012;. Other studies, however, have found the opposite pattern of results, that indicators of approach motivation were more relevant to eating pathology than indicators of avoidance motivation (Clarke, Ramoz, Fladung, & Gorwood, 2016;Dondzilo et al, 2017;Rodgers, DuBois, Frumpkin, & Robinaugh, 2018). It should be noted that this research area is complicated by measurement issues.…”
Section: Fear Of Self In Eating Disorders 11supporting
confidence: 88%
“…Third, while body image distortion consists of both attitudinal (BD) and perceptual (BSSM) components, some early studies failed to find significant associations between the two (Thompson & Gardner, ), suggesting that changes in the perceptual component may not necessarily be accompanied by changes in the attitudinal component. More recently, it has been shown that increased rumination mediates the relationship between selective attention to thin bodies and BD (Dondzilo, Rieger, Palermo, Byrne, & Bell, ) and directing attention to thin idealised bodies does not increase rumination (Dondzilo et al, ). Fourth, the BD scale used in the current study did not specify the timescale to which participants should respond (Thompson, ).…”
Section: Discussionmentioning
confidence: 99%